Respon Awal Tanaman Kangkung Terhadap Penyiraman Air Cucian Beras Selama Satu Hari - Herni Jelita Halawa (CV. SINAR HOWUHOWU, 2025)
Response of kangkung (Ipomoea aquatica Forsk.) to irrigation with rice washing water over a 24-hour period in Gunungsitoli. Sustainable agriculture increasingly emphasizes the use of natural resources, and rice washing water is known to contain essential nutrients for plants. The research aims to identify early physical changes in plant height and leaf count, as well as the visual condition of kangkung after the application of rice washing water. The method used was a controlled experiment with two groups: control (irrigated with plain water) and treatment (irrigated with rice washing water), each with replications. Plant height measurements and leaf counts were taken at the start and after 24 hours of treatment, accompanied by visual observations. Results indicated a slight average increase in plant height for the treatment group (0.2 cm) compared to the control (0.1 cm) within 24 hours. However, no significant change in leaf count was observed for both groups. Visually, plants treated with rice washing water appeared slightly brighter. While this response is minimal, the study suggests the potential of rice washing water as an early growth stimulant and highlights the importance of longer observation durations for a comprehensive understanding of its nutritional impact.